2022
DOI: 10.1155/2022/3187858
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Route Discovery Mechanism Using Improved CH Selection Using Q-Learning to Minimize Delay

Abstract: With the technological advancements, practical challenges of establishing long-distance communication should be addressed using hop-oriented routing networks. However, long-distance data transmissions usually deteriorate the quality of service (QoS) especially in terms of considerable communication delay. Therefore, in the presented work, a reward-based routing mechanism is proposed that aims at minimizing the overall delay which is evaluated under various scenarios. The routing process involved a refined CH s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Based on reinforcement learning's Q learning model, the authors suggested an enhanced route discovery process. This is used to enhance the reward-based learning mechanism thereby improving the QoS parameters and decreasing the delay observed while overall communication is performed in WSN [40].…”
Section: Authors Proposed a New Technique Named Esrt A New Trust And ...mentioning
confidence: 99%
“…Based on reinforcement learning's Q learning model, the authors suggested an enhanced route discovery process. This is used to enhance the reward-based learning mechanism thereby improving the QoS parameters and decreasing the delay observed while overall communication is performed in WSN [40].…”
Section: Authors Proposed a New Technique Named Esrt A New Trust And ...mentioning
confidence: 99%
“…Smart farming IoT uses are shown in Figure 1. Farm monitoring, precision farming, supply chain management, tracking and tracing, forest monitoring, and UAV farming are a few of the applications [9]. High agricultural production and resource-efficient practices in farming and agriculture may increase production.…”
Section: Introductionmentioning
confidence: 99%